Optimization method for simultaneous extraction and detection of imazapic and imazapyr herbicides in soil and water using HPLC-UV with verification of LC-MS - Bajrai F.S.M.,; Ismail B.S.,; Mardiana-Jansar K., (Penerbit Universiti Kebangsaan Malaysia, 2017)
The residual activity of herbicides in soil and water may be detrimental to the environment. This issue has caught the attention of environmentalists and among the herbicides concerned are a mixture of Imazapic and Imazapyr, also known as OnDuty®, which is currently being used in the Clearfield® Production System. These herbicides are widely used to control weedy rice in rice fields. In order to determine their residues in both soil and water, an accurate and simple method of extraction has to be developed. In the present study, extraction processes followed by HPLC-UV separation was developed and validated for simultaneous determination of imazapic and imazapyr in two matrices, namely soil and water. Verification of chemical compounds was then determined by using LC-MS (ToF). Recovery values of imazapic and imazapyr using 10 μM ammonium acetate extraction from blank samples spiked at levels between 1 mg L-1 and 10 mg L-1 in soil and water were 83% to 106% (with RSD ≤9%). The limit of detection (LOD) ranged from 0.25 to 0.46 mg L−1 while the limit of quantification (LOQ) was from 0.74 to 1.37 mg L-1. LC-MS (ToF) mass spectrum analyses of imazapyr and imazapic were obtained at m/z 262.12 with the retention time of 2.39 min and m/z 276.13 with the retention time of 3.06 min, respectively. This method would be helpful in determining the level of pesticides in soil and water in a shorter time (< 6 min).